Sexual conflict and the evolution of nuptial feeding - Jalinsky, Joseph Ryan (Kansas State University, 2014)
Males providing females with gifts in order to mate is not a novel occurrence. Indeed, depending on the taxonomic system, males may provide gifts ranging from dead insects, to nutritious ejaculates to even subjecting themselves to cannibalistic feeding. Interestingly, while the burden of the costs of these gifts is primarily carried by the male, net fitness of providing or receiving such gifts must be positive for both sexes, if these gifts are to be maintained in a population. If this is not the case, and sexual conflict has exerted a cost-benefit imbalance between the sexes, then the expectation is that the system will evolve towards the reduction of nuptial gift giving. Here, utilizing the Allonemobius socius complex of crickets where females benefit greatly from cannibalizing male blood as a nuptial gift, we explore the possibility that sexual conflict is acting on gift size. To do this, we assess the gift-size distribution, and their associated fitness functions, for twelve populations that span the phylogeny and geographic distribution of this complex. We find that gift-size distributions are shifted towards small or no gifts in the majority of populations. Moreover, fitness data suggest that males providing a small or even no gift are equally successful to their large gift-giving counterparts. Taken together, the population profiles indicate that at least half of these populations are evolving towards the near or complete loss of these cannibalistic gifts – a predicted, but previously undocumented, outcome of sexual conflict. We also assess the speed at which sexual conflict is acting to alter gift size distributions in populations by comparing gift sizes between different time points in populations and across phylogenetic history. The implications of these results are discussed relative to antagonistic coevolution of behavioral traits and sexual conflict theory in general.
Keywords: Sexual Conflict; Nuptial Feeding; Allonemobius; Biology (0306)